PENGARUH VARIAN FRAKSI VOLUME SERAT RESAM DAN SERBUK KAYU SERUK/ MEDANG GATAL TERHADAP UJI TARIK DAN UJI IMPACT KOMPOSIT - Dewa Eza Adriyan Suwanto; Muhammad Subhan; Indah Riezky Pratiwi (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Resam itself is a wild plant that commonly grows around shady and moist cliffs, resam plants can be found in almost all tropical and subtropical regions in Asia. Previous research using resam fibers as composite reinforcement materials showed that resam fibers have an effect on tensile strength and impact strength based on NaOH treatment. Therefore, the purpose of this study is to utilize resam fiber as a composite reinforcement material. Not only resam fiber, this study also utilizes shaved wood powder / itchy field as a composite strengthening added material. The method used in this study is a factorial experimental method, where the parameters used are variants of fiber volume fraction and wood powder. The volume fraction variant used is 8% fiber: 4% wood powder, 6% fiber: 6% wood powder, 4% fiber: 8% wood powder. The results of tensile testing showed the highest tensile strength was located at a percentage of 8% fiber: 4% of wood powder was 14.5 MPa and the lowest tensile strength was located at 4% of fiber: 8% of wood powder was 12.64 MPa. While the results of impact testing showed the highest impact strength was at a percentage of 8% fiber: 4% wood powder which is 35.52328 Kg /² and the lowest impact strength was located at a percentage of 4% fiber : 8% wood powder which is 23.4041 Kg / mm ².